Compact Balanced Dual- and Tri-Band BPFs Based on Coupled Complementary Split-Ring Resonators (C-CSRR) - Wei, Feng; Qin, Pei-Yuan; Guo, Y. Jay; Ding, Chen; Shi, Xiao Wei (IEEE microwave and wireless components letters, 2016)
Two multi-band balanced bandpass filters (BPFs) are proposed by embedding multi-band coupled complementary split- ring resonators (C-CSRRs) into a balanced stepped-impedance microstrip-slotline transition structure. The proposed C-CSRR is made from two or three nested CSRRs with a pair of coupling slotlines in the open end of each ring, which can result in dual-band or tri-band bandpass responses, respectivley. It is found that a high and wideband common-mode (CM) suppression can be achieved for the proposed filters. Moreover, the center frequencies of the differential-mode (DM) passbands are independent from the CM responses, which significantly simplify the design procedure. In order to validate its practicalbility, two balanced BPFs with two and three DM passbands are fabricated and good agreement between simulated and measured results is observed.